The Impact of Consumer Search Cost on Assortment Planning and Pricing - Wang, Ruxian; Sahin, Ozge (Management Science, 2018)
Consumers search for product information to resolve valuation uncertainties before purchase. We incorporate search cost into consumer choice models and study the two-stage consider-then-choose policy. In the first stage, a consumer forms her consideration set by balancing utility uncertainty and search cost. In the second stage, she evaluates all products in her consideration set and chooses the one with the highest net utility. We show that the revenue-ordered assortment (i.e., the offer set that includes products in the revenue-decreasing order) fails to be optimal, although it can obtain at least half the optimal revenue. We propose a k-quasi-attractiveness-ordered assortment and show that it can be arbitrarily near optimal for the market share maximization problem. The assortment problems with search cost are generally NP-hard, so we develop efficient approximation or relatively fast exact algorithms for a variety of assortment problems under the consider-then-choose models with search cost. For the joint assortment planning and pricing problem with homogeneous consumers, we show that the intrinsic-utility-ordered assortment and the quasi-same-price policy, which charges the same price for all products except at most one, are optimal. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2790 . This paper was accepted by Gad Allon, operations management.